Catalizador de Jacobsen inmovilizado en Al-MCM-41 y en Si-MCM-41 modificada con grupos amino y su actividad en la epoxidación enantioselectiva heterogénea utilizando dimetildioxirano generado in situ como oxidante - Cubillos, Jairo; Hölderich, Wolfgang (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
The enantioselective epoxidation of three prochiral oleﬁns over Jacobsen’s catalyst immobilized on Al-MCM-41 and NH2-Si-MCM-41 in the presence of in situ generated DMD as the oxygen source was investigated. Experimental results indicate that the catalyst did not signiﬁcantly suffer any change in its chemical structure. Therefore, the reusability of catalyst could be successfully achieved when it was immobilized by chemical bonding of the salen ligand.